An uncommon histopathological diagnosis. Issue 4 (December 2018) - Bode, Hannelore; Sciot, Raf; Werbrouck, Emilie; Geusens, Eric; Deroose, Christophe M.; Nackaerts, Kristiaan
An 81-year-old woman presented to the emergency department because of a recent sharp pain in the left hemithorax and a history of recurrent lower respiratory tract infections. She had been treated with antibiotics twice during the last month before presentation. She was a never-smoker with a previous history of depression and complete thyroidectomy for a nontoxic multinodular goitre. Can you perform a robust histopathological diagnosis for this unusual case?  http://ow.ly/40GB30mc5Th